Identification and Integrated Analysis of MicroRNA and mRNA Expression Profiles During Agonistic Behavior in Chinese Mitten Crab (Eriocheir sinensis) Using a Deep Sequencing Approach - Pang, Yangyang; He, Long; Song, Yameng; Song, Xiaozhe; Lv, Jiahuan; Cheng, Yongxu; Yang, Xiaozhen (Frontiers in Genetics, 2020)
As a commercially important species, the Chinese mitten crab (Eriocheir sinensis) has been cultured for a long time in China. Agonistic behavior often causes limb disability and requires much energy, which is harmful for the growth and survival of crabs. In this paper, we divided crabs into the control group (control, no treatment) and experimental group (fight, agonistic behavior after 1 h) and then collected the thoracic ganglia to extract RNA. Subsequently, we first use a deep sequencing approach to examine the transcripts of microRNAs and mRNAs in E. sinensis displaying agonistic behavior. According to the results, we found 29 significant differentially expressed miRNAs (DEMs) and 116 significant differentially expressed unigenes (DEGs). The DEMs aca-miR-199a-5p, pma-let-7d, efu-miR-200a and efu-miR-200b may participate in the regulation of agonistic behavior by mediating neuro-regulation and energy metabolism. Focusing on the transcripts of the mRNAs, the renin-angiotensin system KEGG pathway may be involved in the regulation of agonistic behavior through glucose metabolism as this pathway was significantly enriched with DEGs. In addition, an integrated analysis of the miRNA and mRNA profiles revealed that the retinoid X receptor (RXR) is also involved in visual signal transduction, which is important for agonistic behavior. In addition, four vital agonistic behavior-related metabolic pathways, including the cAMP signaling, MAPK, protein digestion and absorption and fatty metabolism pathways, were significantly enriched with the predicted target unigenes. In conclusion, the findings of this study may provide important insight enhancing our understanding of the underlying molecular mechanisms of agonistic behavior in E. sinensis.